Chloroquine/ hydroxychloroquine prevention of coronavirus disease (COVID-19) in the healthcare setting; protocol for a randomised, placebo-controlled prophylaxis study (COPCOV) - Schilling, WHK; Callery, JJ; Taylor, W; Mukaka, M; Ekkapongpisit, M; Watson, JA; Chandna, A; Panapipat, S; Tubprasert, J; Yuentrakul, P; Waithira, N; Cope, T; et al. (F1000 Research Ltd, 2020)
There is no proven preventative therapy or vaccine against COVID-19. Theinfection has spread rapidly and there has already been a substantial adverse impact on the global economy. Healthcare workers have been affected disproportionately in the continuing pandemic. Significant infection rates in this critical group have resulted in a breakdown of health services in some countries. Chloroquine, and the closely related hydroxychloroquine, are safe and well tolerated medications which can be given for years without adverse effects. Chloroquine and hydroxychloroquine have significant antiviral activity against SARS-CoV-2, and despite the lack of benefit of hydroxychloroquine treatment in patients hospitalised with severe COVID-19, these drugs could still work in prevention. The emerging infection paradigm of an early viral peak, and late inflammation where there is benefit from corticosteroids. If these direct actiing antivirals are to work, they have the best chance given either early in infection and before infection occurs. We describe the study protocol for a multi-centre, multi-country randomised, double blind, placebo controlled trial to answer the question- can chloroquine/ hydroxychloroquine prevent COVID-19. 40,000 participants working in healthcare facilities or involved in the management of COVID-19 will be randomised 1:1 to receive chloroquine/ hydroxychloroquine or matched placebo as daily prophylaxis for three months. The primary objective is the prevention of symptomatic, virological or serologically proven coronavirus disease (COVID-19). The study could detect a 23% reduction from an incidence of 3% in the placebo group for either drug with 80% power. Secondary objectives are to determine if chloroquine/hydroxychloroquine prophylaxis attenuates severity, prevents asymptomaticCOVID-19 and symptomatic acute respiratory infections of another aetiology (non-SARS-CoV-2).